Malawi : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2004)
This report presents an ex post assessment of Malawi's longer-term program engagement with the IMF. Given the length of the engagement, and the important political change that took place in the mid-1990s, much of this report focuses on performance during the programs supported by the 1995 Enhanced Structural Adjustment Facility and 2000 Poverty Reduction and Growth Facility arrangements. It provides an overview of economic developments, and reviews achievements and shortcomings in some key macroeconomic and structural areas. The role of the IMF in this process is also analyzed.